MODEL LATIHAN JUMP SHOOT BOLA BASKET PADA ATLET PEMULA - Dwi Asih Lestari; Hasan Basri; Dindin Abidin (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2022)
The purpose of this study was to determine the effect of implementing the basketball jump shoot exercise model on novice athletes, to find out the increase in jump shoot training results through the basketball jump shoot training model for beginners which was developed and to produce a product in the form of a basketball jump shoot exercise model. The research was conducted in the North Jakarta basketball club environment. The research method used is Research & Development research. This model development research is designed using Research & Development research which will produce a jump shoot exercise model in basketball. The results of the validation of the basketball expert 1 can be concluded that a score of 27 is obtained from a maximum score of 28 and the percentage obtained is 96% where the score belongs to the appropriate or good category, then the results of the validation of the basketball expert 2 can be concluded that the score is 26 from a maximum score of 28 and the percentage which obtained 93% where the score was included in the decent or good category, and the results of motor expert validation can be concluded that the score is 27 out of a maximum score of 28 and the percentage obtained is 96% where the score is included in the decent or good category.